Legal Protection Against Victims Of Child Sexual Exploitation In The City Of Yogyakarta In The Digital Space From A Human Rights Perspective - Laksmi, Nareswari Diah Cintya; Islami, Muhammad Nur (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to look at forms of recovery efforts for children as victims of sexual exploitation in the digital realm and concepts in dealing with criminal acts of sexual exploitation in the digital realm. The method in this research is normative legal research. Normative legal research is also called doctrinal legal research. In normative research, law is often conceptualized as what is written in statutory regulations. This research is normative because it seeks to place law as a system of norms built on and related to principles, standards, rules of statutory regulations, and decisions. Courts, agreements and doctrines (teachings). The research results show that legal protection for victims of child sexual exploitation in the city of Yogyakarta in the digital realm requires a holistic and integrated approach, which is based on human rights principles. This approach includes efforts to strengthen existing regulations, develop inclusive policies, increase public awareness, and use technology as an innovative tool in combating child sexual exploitation. Legal protection must also pay attention to the recovery of victims, both directly and indirectly, through assistance, legal and psychological counselling, and holistic rehabilitation assistance. Cross-sector collaboration between governments, law enforcement agencies and online platforms is also essential to ensure adequate protection. Apart from that, the future concept in dealing with criminal acts of sexual exploitation in the digital realm involves strengthening regulations, strict law enforcement, and integrating child protection principles into applicable law.